Safe firefighting : - Kidd, Steve (McGraw-Hill, 2007)
This book talks about an training firefighting program. It is divided into three main levels of training, each progressively building upon the previous one as you proceed. The outcome we all want is a competent firefighter _ a firefighter who will safely and efficiently perform the best possible job.